Dynamical Study of a Constant Viscous Dark Energy Model in Classical and Loop Quantum Cosmology*Supported by the Algerian Ministry of Education and Research, and DGRSDT. (May 2016) - Benchikh, Sara; Mebarki, Noureddine; Aberkane, Dalel
Abstract : Dynamical behaviors and stability properties of a flat space Friedmann–Robertson–Walker universe filled with pressureless dark matter and viscous dark energy are studied in the context of standard classical and loop quantum cosmology. Assuming that the dark energy has a constant bulk viscosity, it is found that the bulk viscosity effects influence only the quintessence model case leading to the existence of a viscous late time attractor solution of de-Sitter type, whereas the quantum geometry effects influence the phantom model case where the big rip singularity is removed. Moreover, our results of the Hubble parameter as a function of the redshift are in good agreement with the more recent data.